Pengaruh Kebisingan Dalam Ruang Control Tower Terhadap Pelayanan Lalulintas Penerbangan Di Bandara Sentani Jayapura - Nur, Mulyadi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2019)
In the provision of air traffic services, ATC (Air Traffic Controller) officers are requiredto ensure safety and smoothness in accordance with the procedures for flight safety can beachieved. The case of Kelas I Khusus Sentani Jayapura Airport is the noise caused by theapron building which is quite close to the tower building and the propeller type plane thatpasses the bravo taxiway causing quite disturbing noise. The purpose of this research is toprovide optimal air traffic service related to controller comfort in providing flight trafficservice, using qualitative deskriktif method based on field observation and related documenton air transport service provision in order to create flight safety and security. The results ofthis paper indicate that noise can affect the convenience of the controller when providing airtraffic services in terms of safety and regularity of the flight. It is suggested to AIRNAV andKelas I Khusus Sentani Jayapura Airport managers should install carpet and rubber silencerin tower building to reduce noise.